Sphincter-saving surgery after neoadjuvant therapy for ultra-low rectal cancer where abdominoperineal resection was indicated: 10-year results of the GRECCAR 1 trial. Issue 1 (16th December 2020) - Rouanet, P; Rivoire, M; Gourgou, S; Lelong, B; Rullier, E; Jafari, M; Mineur, L; Pocard, M; Faucheron, J L; Dravet, F; Pezet, D; Fabre, J M; et al.
Abstract : This phase III trial included patients with ultra-low rectal adenocarcinoma that initially required abdominoperineal resection. The surgical decision was based on clinical tumour status after preoperative treatment. The overall sphincter-saving resection rate was 85 per cent, with 72 per cent rate of intersphincteric resection. Long-term results showed that changing the initial abdominoperineal resection indication into a sphincter-saving resection according to tumoral response is oncologically safe. Saving the sphincter